Imaging and Differential Diagnosis of Suprarenal Masses in the Fetus. (1st May 2014) - Maki, Erik; Oh, Karen; Rogers, Sarah; Sohaey, Roya
Abstract : Prenatal sonography and magnetic resonance imaging of suprarenal fetal masses is presented, along with clinical information and follow‐up. Imaging pearls and differential considerations for each diagnosis will be discussed. Fetal suprarenal mass diagnoses include neuroblastoma, extralobar pulmonary sequestration, congenital adrenal hyperplasia, partial multicystic dysplastic kidney, renal duplication, urinoma, gastric duplication cyst, and splenic cyst. Recognizing the range of malignant and benign suprarenal fetal masses that can present on prenatal imaging can help guide patient counseling and management.